Modificación de olfatómetros de cuatro brazos para experimentación en broca del café, Hypothenemus hampei ferrari (Coleoptera: Curculionidae) - Pacheco, Arturo (2013)
Modification of fourarm olfactometers to be used with the coffee borer Hypothenemus hampei Ferrari (Coleoptera: Curculionidae). The coffee berry borer, Hypothenemus hampei is considered to be a major pest in coffee producing countries worldwide. As in many insects, the behavior of the coffee borer is modified through aromatic signals. This has triggered important research within the different approaches of olfactometry. Two new innovative designs of olfactometers were evaluated to be used on H. hampei for this research. The olfactometers were built of glass and differ in the angular distribution of their arms and in the insect’s inlet and adaptation zone. A mixture of methanol-ethanol 3:1, with proven attraction properties, was used to evaluate the functionality of these olfactometers. The bioassays were performed using only adult females of H. hampei. On the 90º olfactometer, 45% of the insects were strongly attracted to the arm comprised of the alcohol mixture. In the case of the 30º olfactometer the positive behavior response was only of 1.5%. During the assays it was observed that the different insect insertion strategies into the olfactometers and the adaptation area had a major influence on results. During the second stage of this research, the 90º olfactometer was evaluated through a comparison of the average attraction of each of its 4 arms; there were no significant differences (p<=0.05) in attraction response of H. hampei between arms of the device. It is concluded that the 90º olfactometer design is suitable to develop volatile-compound attraction assays on adult females of H. hampei.